PRODUKSI HIJAUAN DAN KOMPOSISI KIMIA RUMPUT KUME DAN SUKET PUTIHAN YANG DIINTRODUKSI JENIS LEGUMINOSA BERBEDA (Herbage production and chemical composition of kume grass and suket putihan introduced with different types of legumes) - Dionysius Priyanto; Tara Tiba Nikolaus; I. G. N. Jelantik (JURNAL NUKLEUS PETERNAKAN, 2022)
Low quality and quantity of pasture in East Nusa Tengara is the main problem in development of ruminants. The solution offered to this problem is by using mixed pasture of grass and legume, by consider legume’s advantage in nitrogen fixation, and also it’s capability to provide canopy or shades to grass. The aim of this experiment was to investigate the effect of the introduction of various species of herbaceous legumes on herbage production and the chemical composition of Sorghum plumosum and Bothriochloa pertusa. The research was conducted following a Completely Randomized Design (RCD) with 4 treatments and 3 replications. The treatments tested consisted of Co (Sorghum plumosum and Bothriochloa pertusa), Av (Sorghum plumosum, Bothriochloa pertusa and Alysicarpus vaginalis), Ct (Sorghum plumosum, Bothriochloa pertusa and Clitoria ternatea) and Pp (Sorghum plumosum, Bothriochloa pertusa and Pueraria phaseoloides). The parameters observed were the production of forage, the leaf stem ratio, crude protein, crude fiber, and NDF (Neutral Detergent Fiber). The results showed that the introduction of herbaceous legumes did not affect the production, leaf stem ratio and also the crude protein but does affect the chemical composition of Kume and Suket Putihan such as changes of crude fibre and NDF at the age of 60 days.